Indikator Keberhasilan Pelaksanaan Rencana Pengajaran Pendidikan Jasmani, Olahraga dan Kesehatan SD/MI - Vina Nurwidia; Atma Sri Utami (putrapublisher.org, 2023)
The purpose of this study was to describe indicators of successful implementation of teaching plans for physical education, sports and health in SD/MI. This research method uses descriptive qualitative. This data source uses primary sources, namely from book literature, journal studies, magazines, or websites that support research. This data analysis uses descriptive analysis. The results of this study indicate that indicators of student learning success can be seen from the ability of students to absorb the teaching materials that have been taught and from the actions or behavior outlined in the learning objectives that have been achieved by students, both individually and in groups.